2015 54th IEEE Conference on Decision and Control (CDC) 2015
DOI: 10.1109/cdc.2015.7402879
|View full text |Cite
|
Sign up to set email alerts
|

Counter-Example Guided Synthesis of control Lyapunov functions for switched systems

Abstract: Abstract-We investigate the problem of synthesizing switching controllers for stabilizing continuous-time plants. First, we introduce a class of control Lyapunov functions (CLFs) for switched systems along with a switching strategy that yields a closed loop system with a guaranteed minimum dwell time in each switching mode. However, the challenge lies in automatically synthesizing appropriate CLFs. Assuming a given fixed form for the CLF with unknown coefficients, we derive quantified nonlinear constraints who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 30 publications
(50 reference statements)
0
49
0
Order By: Relevance
“…for the DC-DC boost converter the authors of [33] had to iteratively add barrier functions by hand before a solution was found. Moreover, in our benchmarks we synthesize sampled-data controllers with a larger sampling time than the minimum dwell-times presented in [33,49]. Finally, we are not able to find sampled-data controllers for all systems in Table 1 (systems 3 and 4) as opposed to our previous work [38].…”
Section: Discussionmentioning
confidence: 84%
“…for the DC-DC boost converter the authors of [33] had to iteratively add barrier functions by hand before a solution was found. Moreover, in our benchmarks we synthesize sampled-data controllers with a larger sampling time than the minimum dwell-times presented in [33,49]. Finally, we are not able to find sampled-data controllers for all systems in Table 1 (systems 3 and 4) as opposed to our previous work [38].…”
Section: Discussionmentioning
confidence: 84%
“…In the setting of this paper, however, the use of a MPC scheme as a demonstrator allows us to use faster LP solvers and provide convergence guarantees. Empirically, we are able to demonstrate the successful inference of CLFs on systems with up to eight state variables, whereas previous work in this space has been restricted to much smaller problems [77].…”
Section: Counter-example Guided Inductive Synthesismentioning
confidence: 84%
“…Sontag formula can be extended to systems with saturated inputs where U is an n-ball [53] or a polytope [91]. Also switching-based feedback is possible, under some mild assumptions (to avoid Zeno behavior) [22,77]. We assume dynamics are affine in control and use these results which reduce Problem 1 to that of finding a control Lyapunov function V .…”
Section: Definition 3 (Control Lyapunov Function(clf))mentioning
confidence: 99%
See 1 more Smart Citation
“…In the second phase, a counterexample guided inductive synthesis (CEGIS) framework [26], -an approach that uses SMT solvers at its core -is used to discover such control certificates. However, this procedure is used off the shelf, building upon the previous work of Ravanbakhsh et al [22]. This procedure uses a specialized solver for finding a certificate of a given parametric form that handles quantified formulas by alternating between a series of quantifier free formulas using existing SMT solvers [18,3].…”
Section: Introductionmentioning
confidence: 99%